2009
DOI: 10.1007/s11517-009-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

The augmented RIC model of the human respiratory system

Abstract: This paper describes the augmented RIC model of respiratory impedance and analyzes its parameter values estimated--by a modified Newton method with least squares criterion--from impulse oscillometry data. The data were from asthmatic children, tested pre- and post-bronchodilator, and from healthy adults and a second group of adults with COPD. Our analyses show that the augmented RIC model was 13.7-66.6% more accurate than the extended RIC model at fitting these data, while its parameter estimates were within p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
1
12
0
3
Order By: Relevance
“…Moreover, the impedance values and shape were significantly close to those identified with several parametric models, such as in [16,9]. Additionally, we also looked at the real part of impedance values at 6 Hz, i.e.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the impedance values and shape were significantly close to those identified with several parametric models, such as in [16,9]. Additionally, we also looked at the real part of impedance values at 6 Hz, i.e.…”
Section: Discussionsupporting
confidence: 58%
“…25 E por fim, a Fres, que traduz a frequência com que o tecido pulmonar se move da distensão passiva para extensão ativa em resposta à força do sinal de onda de pressão. 23 As curvas de impedância do IOS, que mostram a relação fluxo-pressão também podem ser correlacionadas 26 , equivalentes com a resistência e a inertância mecânicas em conformidade com o sistema respiratório humano e que podem ser representadas por modelos de circuitos elétricos. 27,28,29 Nesse contexto, e considerando a importância da avaliação da mecânica respiratória na prática clí-nica, a presente revisão tem como objetivo apresentar uma atualização da literatura quanto ao sistema, critérios técnicos e interpretação de dados, bem como a relação do sistema com outros métodos de avaliação respiratória e sua aplicabilidade clínica.…”
Section: Palavras-chavesunclassified
“…This effort to date has demonstrated that the performance of extended Resistance Inductance Capacitance (eRIC) model and the augmented RIC (aRIC) model (an improvement of the eRIC model) ranked in the middle of a series of conventional models developed over the past several decades in terms of total cumulative error. However, they provide parameter estimates that are physiologically more realistic and in line with expected values in normal subjects and those suffering from pulmonary diseases (43)(44)(45)(46)(47)(48)(49)(50)(51), than previous models.…”
Section: Introductionmentioning
confidence: 74%